Estudo da introdução de resíduo de britagem de rocha calcária e cinza de biomassa de cana-de-açúcar em formulações de argamassas colantes - Silva, Walney Gomes da (2014)
The adhesive mortars are a mixture of cement, sand, and additives to polymers that retain the mixing water and promotes adherence, being used in setting on various ceramic substrates. The sand used in the production of these mortars is from the riverbeds, and with the increasing restriction of these sands extraction by environmental agencies, and often having to be transported over long distances to the consumer center. This work aims to design and physical and mechanical characterization of ecological adhesive mortar with total replacement of natural sand by sand from the crushing of limestone, and the addition of mineral ash biomass of cane sugar in partial replacement cement used in the production of adhesive mortar , aiming compositions that meet the regulatory specifications for use adhesive mortar. Standardized tests to determine the tensile bond strength (NBR 14081-4), determination of open time (NBR 14081-3) and determination of slip (NBR 14081-5) were performed. Were also conducted trials squeeze flow in different formulation, the mortar with addition of 15 % gray biomass of cane sugar for cement mortars as well as the total replacement of natural sand by sand limestone crushing, got the best performance among the mortars studied, it was found that the addition of biomass to replace cement is perfectly feasible due to its pozzolanic activity, which contributed to this reduction in the cement matrix formation of adhesive mortar